USE OF PATIENT ASSESSED HEALTH-RELATED QUALITY OF LIFE INSTRUMENTS IN PROSTATE CANCER RESEARCH: A SYSTEMATIC REVIEW OF THE LITERATURE 2002–15. (22nd March 2016) - Torvinen, Saku; Bergius, Susanne; Roine, Risto; Lodenius, Leena; Sintonen, Harri; Taari, Kimmo
Abstract : Objectives: The objectives of this study were to identify and qualitatively describe, in a systematic literature review, published studies that collected prostate cancer patients' health-related quality of life (HRQoL) estimates by using validated, generic instruments. Methods: Systematic searches of the literature were made using the Medline, Cochrane Library, PsycINFO, and CINAHL electronic databases from 2002 to 2015. Results: The search identified 2, 171 references, of which 237 were obtained for full-text assessment; thirty-three of these articles were deemed relevant and included in the systematic review. An indirect valuation method was used in 73 percent ( n = 24) of the studies. The most commonly used HRQoL instrument with an indirect valuation method was the EuroQol (EQ-5D; n = 21), and the second most common was the 15D ( n = 5). A direct valuation method was used in 48 percent ( n = 16) of the studies. Of these, the Visual Analogue Scale (VAS) was the most often used ( n = 10), followed by the Time-Trade-Off ( n = 6). HRQoL scores varied in localized and early stage disease between 0.63 and 0.91, and in advanced or metastatic disease stage between 0.50 and 0.87. There was also variance in the HRQoL instruments and study methods used, which explains the large variance in HRQoL scores between the various disease stages. Conclusions: Although utility and quality-adjusted life-years gained are considered important measures of effectiveness in health care, the number of studies in which utilities of prostate cancer patients have been estimated using generic HRQoL instruments, based on either direct or indirect measurement of HRQoL, is fairly small.